Women’s solidarity initiatives: the experience of a community development bank - Brasil, Kátia Regina Calixto; Marquesan, Fábio Freitas Schilling; Mesquita, Rafael Fernandes de (Revista de Administração da UFSM, 2021)
Purpose: The purpose of this research is to understand the relationship between the granting of microcredit in a community development bank and the performance of female solidarity enterprises. Methodology: This research is descriptive with a qualitative approach and a theoretical-empirical nature. The data were submitted to the content analysis technique for organisation and interpretation of the findings. Findings: From the results, it can be concluded that the granting of microcredit by the community bank can positively influence the performance of female solidarity enterprises, but it has some limiting factors, such as a low credit limit. Originality: This study analyses the relationship between the microcredit concession processes and the development of female solidarity enterprises. Keywords: Microfinance; Community development bank; Women’s solidarity enterprises.